Howard Teichmann papers - Teichmann, Howard; Teichmann, Howard; Teichmann, Howard; Teichmann, Howard; Teichmann, Howard
Correspondence, drafts and typescripts of writings, notes, research material, financial records, photographs, and other papers pertaining to Teichmann's career as a playwright, biographer, educator, and theater administrator. Drafts of Teichmann's books include George S. Kaufman: An Intimate Portrait (1972), Smart Aleck: The Wit, World, and Life of Alexander Woollcott (1976), Alice: The Life and Times of Alice Roosevelt Longworth (1979), Fonda: My Life as Told to Howard Teichmann (1981); and drafts of his play script The Solid Gold Cadillac and of radio scripts. Also includes material pertaining to Teichmann's student years at the University of Wisconsin (Madison, Wisc.); teaching career at Barnard College; work for the U.S. Office of War Information during World War II, the Dramatists Guild and Shubert Theatre Enterprises, Columbia Broadcasting System, inc., and National Broadcasting Company; and partnership agreement with his wife Evelyn Goldstein Teichmann. Includes material pertaining to Milton Shubert's work for the U.S. Navy Dept. during World War II. Correspondents include George Abbott, Imogene Coca, Helen Hayes, John Houseman, George S. Kaufman, Lucy Kroll, Harold Prince, Dore Schary, Roger L. Stevens, Jule Styne, Iphigene Ochs Sulzberger, and Earl Wilson.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Library of Congress Music Division.
Library of Congress Prints and Photographs Division.
Library of Congress Serial and Government Division.
Author, educator, and theater administrator.
Collection material in English.
Keywords: Abbott, George, -- 1887-1995 -- Correspondence; Coca, Imogene -- Correspondence; Fonda, Henry, -- 1905-1982.; Hayes, Helen, -- 1900-1993 -- Correspondence; Houseman, John -- Correspondence; Kaufman, George S. -- 1889-1961.; Kaufman, George S. -- 1889-1961 -- Correspondence; Kroll, Lucy -- Correspondence; Longworth, Alice Roosevelt, -- 1884-1980.; Prince, Harold, -- 1928- -- Correspondence; Schary, Dore -- Correspondence; Shubert, Milton; Stevens, Roger L. -- Correspondence; Styne, Jule, -- 1905-1994 -- Correspondence; Sulzberger, Iphigene Ochs -- Correspondence; Teichmann, Evelyn Goldstein; Wilson, Earl, -- 1907- -- Correspondence; Woollcott, Alexander, -- 1887-1943.; United States. -- Navy Department; United States. -- Office of War Information; Barnard College -- Faculty; Columbia Broadcasting System, inc; Dramatists Guild; National Broadcasting Company; Shubert Theatre Enterprises; University of Wisconsin -- Students; Actors -- Biography; American drama; Authors -- Biography; Children of presidents -- United States -- Biography; Dramatists, American -- Biography; Radio scripts; Radio programs; Television; World War, 1939-1945.; United States -- Biography; Administrators; Authors; Educators